Implementasi Praktik Kerja Lapangan di Masa Pandemi Covid-19 Terhadap Kesiapan Kerja Mahasiswa Prodi Manajemen Pendidikan Universitas Negeri Jakarta - Desi - Rahmawati; Zahra Karenina; Anita Farida; Komala; Wahdiniyah Nur Rohma (Program Studi Manajemen Pendidikan, 2022)
Abstract : In providing opportunities to apply theory and practice in the field, students of Jakarta State University (UNJ) are required to undergo a Field Work Practice (PKL) program tailored to the needs of their respective study programs. PKL activities for UNJ students, which were originally carried out face-to-face in the industry where they were carried out, are now carried out online, this is in accordance with the policies set by the government and universities in line with awareness of the covid-19 virus (UNJ, 2020). Therefore, this study aims to determine the implementation of field work practices (PKL) during the covid-19 pandemic on the work readiness of education management study program students class of 2017, Jakarta State University. This research uses descriptive qualitative methods. The sample in this study were Education Management Students of State University of Jakarta Class of 2017 as students who carried out PKL during the pandemic and PKL coordinator lecturers MP UNJ 2020. The data collection techniques that researchers use are interview techniques, observation and documentation. The results showed that the implementation of field work practices (PKL) during the covid-19 pandemic for UNJ Education management students was carried out by work from home (WFH) and also work from office (WFO), namely adjusting the policies of related agencies. In its implementation, several obstacles were found in the implementation of this blended PKL.